(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study was motivated by the low level of career decision-making skills among students at SMP Negeri 1 Moroo, particularly regarding the selection of further education and career paths aligned with their interests, talents, and personal abilities. The study aimed to determine the effectiveness of group guidance services utilizing problem-solving techniques in enhancing students’ career decision-making skills. A quantitative approach with a One-Group Pretest-Posttest design was employed, involving 28 students from class VIII-A. Data were collected through questionnaires, observation, and interviews, and analyzed using the Paired Samples t-Test. The results revealed that the mean career decision-making score increased from 53.64 in the pretest to 108.96 in the posttest. The Paired Samples t-Test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between the scores obtained before and after the intervention. Thus, group guidance services incorporating problem-solving techniques proved effective in improving students’ career decision-making skills. These findings suggest that problem-solving techniques can serve as a viable alternative for group guidance services to assist students in making decisions regarding their education and career paths.